Mindfulness and self-rated performance among novice athletes in China: a sequential mediating role of flow and cognitive anxiety - Peng, Jian; Jing, Longjun; Wang, Peng; Wang, Huilin (Frontiers in Psychology, 2025)
PurposeThis study explores the relationship between mindfulness, flow, cognitive anxiety, and self-rated performance in competitive sports, moving away from traditional cognitive-behavioral principles to investigate mindfulness-based interventions, specifically mindfulness- and acceptance-based interventions (MABI). The research is centered on understanding how mindfulness relates to the self-rated performance, flow experiences, and cognitive anxiety in novice athletes.MethodsConvenience sampling and snowball sampling were employed to collect cross-sectional data from 315 participants in Changsha, China, during August and September 2023. Utilizing a structural equation model, the study examined the association between mindfulness and the self-rated performance of novice athletes.ResultsMindfulness, flow, and self-rated performance were all negatively correlated with cognitive anxiety, and cognitive anxiety mediated the relationship between flow and self-rated performance. Additionally, flow and cognitive anxiety served as a chain mediation between mindfulness and self-rated performance.DiscussionThe findings suggest that for novice athletes, flow and cognitive anxiety may be crucial mechanisms through which mindfulness improves self-rated performance. When coaches face novice athletes experiencing suboptimal competitive states, they can utilize effective mindfulness practices to enhance the athletes' perception of their performance. This can help novices transition to elite roles and integrate more quickly into the professional sports arena.